Amylases without known homologues discovered in an acid mine drainage: significance and impact - Delavat, François (Nature Publishing Group, 2012)
Acid Mine Drainages (AMDs) are extreme environments characterized by acidic and oligotrophic conditions and by metal contaminations. A function-based screening of an AMD-derived metagenomic library led to the discovery and partial characterization of two non-homologous endo-acting amylases sharing no sequence similarity with any known amylase nor glycosidase. None carried known amylolytic domains, nor could be assigned to any GH-family. One amylase displayed no similarity with any known protein, whereas the second one was similar to TraC proteins involved in the bacterial type IV secretion system. According to the scarce similarities with known proteins, 3D-structure modelling using I-TASSER was unsuccessful. This study underlined the utility of a function-driven metagenomic approach to obtain a clearer image of the bacterial community enzymatic landscape. More generally, this work points out that screening for microorganisms or biomolecules in a priori incongruous environments could provide unconventional and new exciting ways for bioprospecting.